Health Service Use and Treatment Choices for Pediatric Eosinophilic Esophagitis: Findings From a Cross-Sectional Survey of Australian Carers - Hannan, Nicole; Steel, Amie; McMillan, Sara S.; Tiralongo, Evelin (Frontiers in Pediatrics, 2020)
Objectives: The incidence and the prevalence of eosinophilic esophagitis (EoE) are increasing, and healthcare utilization among children with EoE is high. This study provides novel insights into the health services and the treatments, including complementary medicines (CMs), used by carers to manage their children's EoE as well as the carers' beliefs and attitudes toward these treatments. Methods: A national cross-sectional online survey was conducted in Australia between September 2018 and February 2019. The survey included questions about health service and treatment utilization, health insurance and government support, health-related quality of life of children with EoE and their carers, views and attitudes toward CM use, and perceived efficacy of treatment. Results: The survey was completed by 181 carers (96.6% of whom were mothers) of EoE children. Most children (91.2%, n = 165) had seen a medical doctor for their EoE, and almost half had consulted with a CM practitioner (40.3%, n = 73). Pharmaceuticals (n = 156, 86.2%) were the most commonly used treatment option, followed by dietary changes (n = 142, 78.5%), CM products (n = 109, 60.2%), and CM therapies (n = 42, 23.2%). Most children received care from numerous practitioners on multiple occasions, indicating a substantial financial and treatment-related burden. Conclusions: A variety of practitioners are involved in the care of children with EoE, and a high rate of CM use warrants further attention to ensure that appropriate treatment is provided. Carer involvement and guidance, combined with individual practitioner expertise, referrals, and collaboration between providers, is essential to successfully navigate this complex disease and provide adequate care for these patients.